Favorite-longshot bias in pari-mutuel betting: An evolutionary explanation - KAJII, Atsushi (Institutional Knowledge at Singapore Management University, 2017)
Favorite-longshot bias (FLB) refers to an observed tendency whereby “longshots” are overvalued and favorites are undervalued. We offer an evolutionary explanation for FLB in pari-mutuel betting using a simple market model. A bettor is forced to quit with some probability if his total net gain in one day is negative. Because of a positive track take, the expected returns of any strategy are negative, and so every agent must eventually lose and disappear in the long run. Those who favor longshots have a better chance of getting ahead with rare but large gains, enabling them to survive for longer than those who bet on favorites. This relative advantage results in overvaluation of longshots in the long run.